Modulation of Angiotensin II responses in sympathetic neurons by cytosolic calcium - Fernandez, Stanley F. (Ann Arbor Michigan ProQuest Information and Learning Company, 2004)
Both stimulatory and suppressive responses of the sympathetic nervous system to angiotensin II (AII) have been reported in intact animals. To elucidate possible cellular mechanisms, we studied AII-induced changes in cytosolic Ca ([Ca]i) in primary cultures of rat stellate ganglion neurons. Two different patterns of [Ca]i responses to AII were observed: dose-dependent increases in [Ca]i in cells with intrinsically low baseline [Ca]i (n=64) and dose-dependent suppression of [Ca]i in neurons with intrinsically higher baseline [Ca]i (n=46). Individual neurons could express both response patterns to AII. In neurons with low basal [Ca]i, superfusion with Ca ionophore (ionomycin) increased [Ca]i and reversed the initial AII-induced stimulatory pattern. L-type Ca channel antagonism (nifedipine) in neurons with high baseline [Ca]i lowered [Ca]i and reversed the initial AII-induced suppressive response. Both stimulatory and suppressive responses were abolished by AT1 receptor antagonism (losartan). AII-induced stimulatory responses were blocked by IP3 receptor antagonism (2-APB) and by thapsigargin. AII-induced suppression of neuronal [Ca]i was blunted when Na-Ca exchange was impaired. We conclude that [Ca]i acts as a switch for AII-mediated stimulatory and suppressive responses in individual sympathetic neurons. AT1 receptor-mediated neuronal stimulation and suppression may allow local homeostatic adaptation to meet complex systemic needs.
Thesis (Ph.D.)--The State University of New York, 2004.
Keywords: Molecular aspects; Cardiovascular system